Techniques to Increase Responsibility for Thesis Completion through Wants, Doing and Direction, Evaluation, and Planning (WDEP) - Astiwi Kurniati; Arie Supriyatna (Budapest International Research and Critics University, 2022)
The problem with this research is that students do not have the responsibility to complete the final project. This study aims to determine the effectiveness of group counselling using the Reality of Wants, Doing and Direction, Evaluation, Planning (WDEP) technique to increase the responsibility for completing the thesis. This study uses an experimental design with a pre-post-test control group design. The research process was carried out by measuring twice (pre-test) before the treatment (treatment) and after (post-test) in the experimental group and the control group. The data collection instrument used a questionnaire to measure the level of student responsibility in completing the thesis. The subjects selected in this study were guidance and counselling students at the University of Muhammadiyah Magelang who were completing their theses, totalling 14 students. The characteristics of the subjects in this study were: a lack of ability to manage time, low fighting power, and feeling afraid and anxious when going to do mentoring with supervisors. Based on the results of the statistical calculation of the hypothesis testing, if the t-arithmetic value is 2.003, then the t-table value is 1.782 with a df of 12 and a significance level of 5%. Based on these results, it can be concluded that the t-count value is greater than the t-table value. This result shows that the reality group counselling technique of Wants, Doing and Direction, Evaluation, Planning (WDEP) is effective in increasing the responsibility for completing the thesis.